Mapping at the nanometer scale the effects of sea-salt derived chlorine on cinnabar and lead white by using delayed image extraction in ToF-SIMS. Issue 7 (3rd March 2021) - Iorio, M.; Sodo, A.; Graziani, V.; Branchini, P.; Casanova Municchia, A.; Ricci, M. A.; Salvadori, O.; Fiorin, E.; Tortora, L.
Abstract : In this work, an innovative analytical approach focused on the use of advanced imaging techniques for the chemical mapping of degradation and/or restoration products is proposed. Abstract : In this work, an innovative analytical approach focused on the use of advanced imaging techniques for the chemical mapping of degradation and/or restoration products is proposed. A representative cross-section showing a very complex stratigraphy from the Saint Wilgefortis Triptych (Hieronymus Bosch), exhibited in the Galleria dell'Accademia di Venezia, was investigated. Time-of-flight secondary ion mass spectrometry (ToF-SIMS) experiments were performed using a time-of-flight detector operating in the so-called delayed extraction mode. The time delay applied during the extraction of the secondary ions permitted mass spectra to be obtained with an excellent mass resolution and chemical maps with nanometer scale spatial resolution. The painting's cross-section was also analysed at the micrometer scale by micro-Fourier transform infrared spectroscopy (micro-FTIR). The combined analytical approaches highlighted the colocalization of lead chloride, oxychloride, and hydroxychloride ions, suggesting the transformation of lead white ((PbCO3 )2 Pb(OH)2 ) into laurionite (PbClOH). Furthermore, chlorine appears evenly diffused in the cinnabar (HgS) layer, inducing the alteration of its more external part into calomel (Hg2 Cl2 ). In fact, from the chemical maps the presence in the sample of an unaltered portion of the cinnabar layer is evident. Such degradation products were probably due to the exposure of the painting to a chloride-rich atmosphere for a long time. This led to a global blackening of the painting. To protect the painting from aggressive chemical species, siloxane compounds were probably used as a modern restorative treatment. ToF-SIMS chemical maps revealed permeation of the silicon-based consolidants within the sample's cracks and no interaction products with the other constitutive materials of the painting were found. Finally, the presence of different lead soaps was detected in correspondence with the lead white layer.